(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2021)
The aboriginal peoples of Malaysia, the orang asli, belong three main groups, namely the Senoi, Negrito and Proto Malays. The Che Wong is a tribe belonging to the Senoi peoples. A large portion of the Che Wong tribe live in Pahang, especially in villages in the areas of Sungai Enggang in Kuala Gandah, Pahang. Based on observation, the Malay language, as a dominant communication language, has influenced the language of the Che Wong tribe. This study focuses on the aspects of the Che Wong language as a medium of communication in Kampung Sungai Enggang, in Kuala Gandah, Pahang. The informants for this study were native speakers of the Che Wong community. The objective of this study was to explain the phonological and lexical aspects of the Che Wong language, using the approach of structural linguistics. The researcher employed a qualitative approach to analyse data obtained through recordings and pronunciation techniques. Transcription was done using symbols of the International Phonetic Alphabet (IPA), with Che Wong vocabulary data based on the Swadesh list and themed word classes. From the analysis, it is found that the Che Wong language has eight vocal phonemes and 20 consonantal phonemes. Based on the themed lexical items, the research also found that there are similarities and differences between the Che Wong and Malay languages. In the themed vocabulary data concerning household items, especially, there are similarities between the Che Wong and Malay languages. However, on the whole, the vocabulary retains much of the Che Wong language. A study of the Che Wong language covering phonological and lexical aspects should be performed to further examine the structure of this language, and to ensure its survival over time. Keyword : Orang asli, Che Wong, Senoi, language, phonology, lexical